TANGGAPAN TERHADAP SERVICE QUALITY DAN KEPUASAN PELANGGAN TERHADAP PELAYANAN WAITER/SS DI NOSTIMO RESTO HOTEL HORAIOS MALIOBORO YOGYAKARTA - Ismawan, Arengga Theo; Hendriyati, Lutfi; Krestanto, Hery (AKPARDA, 2023)
The purpose of this research is to find out how customer's response of service quality at Nostimo Resto Hotel Horaios Malioboro Yogyakarta and how satisfied the customer with the service at Nostimo Resto Hotel Horaios Malioboro Yogyakarta. The research method used is descriptive quantitative data analysis techniques. The research data was obtained from a questionnaire given to 50 respondents who used the services of Nostimo Resto Hotel Horaios Malioboro Yogyakarta. Based at the consequences of the study,, the average of customer's response to service quality showed very good results and the average customer's response to service satisfaction showed very satisfied results.